Effects of Fermented Lingonberry Juice Mouthwash on Salivary Parameters-A One-Year Prospective Human Intervention Study - Pirjo Pärnänen; Sari Lomu; Ismo T. Räisänen; Taina Tervahartiala; Timo Sorsa (MDPI AG, 2022)
A one-year prospective human intervention study was performed to examine the effects of fermented lingonberry juice (FLJ), used as a mouthwash for six months, on salivary parameters. A total of 25 adult participants used 10 mL of FLJ as mouthwash 30 s daily for 6 months in addition to their normal oral homecare routines. Standard oral examinations and gathering of samples were performed at the beginning of the study and after six months and one year. Resting and stimulated saliva secretion rates, resting saliva pH, and stimulated saliva buffering capacity were determined. A questionnaire of participants' subjective sensations of mouth dryness was also recorded at each timepoint. Fermented lingonberry juice mouthwash had positive effect to all five salivary parameters and were, according to the omnibus test, statistically significant during the study period. Analysis of the subjective dry mouth sensation questionnaires revealed that symptoms of xerostomia decreased due to the use of FLJ. This study revealed that the once-a-day use of FLJ mouthwash had a beneficial, increasing effect on salivary flow rates, buffering capacity, and salivary pH. FLJ thus can be safely used as an adjunctive and beneficial therapy in oral homecare, protecting teeth and oral mucosa, including periodontium, and also relieving dry mouth symptoms.